Total Body Skin Examination Practices: A Survey Study Amongst Dermatologists at High-Risk Skin Cancer Clinics - Shirin Bajaj (Mattioli1885, 2019)
Background/Objectives: Although total body skin examination (TBSE) is the primary screening mechanism for melanoma, there is no consensus on which anatomic sites a screening TBSE should include. We sought to establish which anatomic sites are examined during routine (>90%) TBSEs of patients at high risk for skin cancer.